2023
DOI: 10.3390/ijms24065256
|View full text |Cite
|
Sign up to set email alerts
|

Fer and FerT: A New Regulatory Link between Sperm and Cancer Cells

Abstract: Fer and its sperm and cancer specific variant, FerT, are non-receptor tyrosine kinases which play roles in cancer progression and metastasis. Recent studies have shed light on the regulatory role of these kinases in ensuring proper sperm function. Comparison of the regulatory cascades in which Fer and FerT are engaged in sperm and cancer cells presents an interesting picture, in which similar regulatory interactions of these enzymes are integrated in a similar or different regulatory context in the two cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Reactive oxygen species (ROS) are formed during sperm capacitation, which is important for the activation of CaMKII [12] and PLD [31]. Our group showed that treatment of bovine sperm with 50 µM H 2 O 2 causes a significant increase in CaMKII phosphorylation/activation, a state that is completely reversed by 100 µM H 2 O 2 [71]. In human sperm, the addition of SOD causes a decrease in the sAR [72].…”
Section: Role Of Reactive Oxygen Species (Ros) and Mitochondrial Acti...mentioning
confidence: 99%
“…Reactive oxygen species (ROS) are formed during sperm capacitation, which is important for the activation of CaMKII [12] and PLD [31]. Our group showed that treatment of bovine sperm with 50 µM H 2 O 2 causes a significant increase in CaMKII phosphorylation/activation, a state that is completely reversed by 100 µM H 2 O 2 [71]. In human sperm, the addition of SOD causes a decrease in the sAR [72].…”
Section: Role Of Reactive Oxygen Species (Ros) and Mitochondrial Acti...mentioning
confidence: 99%